2017
DOI: 10.15291/lib.907
|View full text |Cite
|
Sign up to set email alerts
|

Kultura putovanja mladih u Hrvatskoj i omladinski turizam

Abstract: Tourism latterly experiences significant changes and growth in all segments. Market demands and sophisticated tastes have led to necessity of providing diversified supply adapting individually to each tourist. In this process specific interests tourism are developing, which according to their characteristics attract and satisfy different profiles of tourists. Specificity of tourism offer and consequently tourism demand reflect in youth tourism, segmented primarily by age, but certainly by specific stylelife an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A questionnaire containing 33 items captured socio-demographic information, motives, activities undertaken in the destination, travel characteristics, attitudes regarding sustainability issues and the importance young people attach to certain characteristics when choosing a travel destination. The items were adapted from previous researches: Buffa, 2015;Hancuk et al, 2020;Klarin & Gusić, 2013;Bubalo-Živković & Lukić, 2015;Moisa, 2010b;Tomić & Božić, 2015;Wangari Njagi et al, 2017;WYSE Travel Confederation, 2018;Šaparnienė et all, 2022;Šimková & Holzner, 2014. Data were analysed using SPSS 25.0. Descriptive analysis provided the profile of the sample.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A questionnaire containing 33 items captured socio-demographic information, motives, activities undertaken in the destination, travel characteristics, attitudes regarding sustainability issues and the importance young people attach to certain characteristics when choosing a travel destination. The items were adapted from previous researches: Buffa, 2015;Hancuk et al, 2020;Klarin & Gusić, 2013;Bubalo-Živković & Lukić, 2015;Moisa, 2010b;Tomić & Božić, 2015;Wangari Njagi et al, 2017;WYSE Travel Confederation, 2018;Šaparnienė et all, 2022;Šimková & Holzner, 2014. Data were analysed using SPSS 25.0. Descriptive analysis provided the profile of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, young people also use their savings, scholarships, student loans, partners, or boyfriends/girlfriends for travel (Carr, 2005). Research by Klarin and Gusić (2013) showed that Croatian youth are not considered "big spender youth", as the majority spend between 133 and 199 euros per trip. Regarding Serbs, Božić and Tomić (2015) found that one of the main barriers to travel is the poor economic situation throughout the country.…”
Section: Literature Backgroundmentioning
confidence: 99%
See 2 more Smart Citations